Glimepiride induced Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH): A case report - Afia Zainab Tanni; Md Farid Uddin; Shohael Mahmud Arafat; Shahjada Selim; Marufa Mustari; MSI Tipu Chowdhury (Global Journal of Medical and Clinical Case Reports - Peertechz Publications, 2022)
The Syndrome of Inappropriate Antidiuretic Hormone Secretion (SIADH) is an important cause of hyponatremia in hospitalized patients and can be caused by a variety of drugs. SIADH is a recognized side effect of 1st generation sulfonylurea (Chlorpropamide) due to its effect on vasopressin secretion. Here we described a 55-year-old woman with uncontrolled type 2 diabetes on glimepiride with SIADH presenting with anorexia, asthenia, and altered mental status. After the withdrawal of glimepiride, these symptoms were improved and sodium level returned to a normal value which demand monitoring of serum sodium level during treatment with glimepiride.